Women Living With Osteoporosis: A Meta-Synthesis. (26th December 2019) - Shorey, Shefaly; Chan, Valerie
Abstract: Background and Objectives: The experiences and needs of individuals with osteoporosis, especially among women, are poorly understood. This meta-synthesis aimed to examine the experiences and needs of women living with osteoporosis. Research Design and Methods: Six databases were searched for qualitative studies from each database's inception to July 18, 2019. Qualitative data were meta-summarized, then meta-synthesized. Results: A total of 2, 781 studies were obtained, and 2, 768 studies were screened after the removal of 13 duplicates. Two thousand seven hundred and sixty studies failed to meet the eligibility criteria, resulting in the inclusion of eight studies in this meta-synthesis. Three themes emerged: (a) physical and psychological consequences of living with osteoporosis, (b) coping strategies to "live better" with osteoporosis, and (c) sources of support and support needs. Discussion and Implications: Women living with osteoporosis experienced negative physical and psychological consequences that led to changes in their lives, particularly in their relationships. They adopted various coping strategies such as acceptance and engaging in doing things that they loved. They expressed support needs such as educational and self-help groups that may help them to cope better. As the included studies were only from the West, more studies from geographically diverse backgrounds such as the Middle East and Asia are required to explore the experiences and needs of women living with osteoporosis. Theory-based health services that incorporate active coping strategies such as self-seeking behaviors should be designed to create awareness about osteoporosis to assist such women in maintaining their independence and overall well-being to age gracefully.